Social Ecological Resilience System of Ambon Island Protected Forest, Maluku Province, Indonesia - Parera, Evelin; Purwanto, Ris Hadi; Permadi, Dwiko Budi; Sumardi, Sumardi (Jurnal Penelitian Kehutanan Wallacea, 2024)
Humans and nature cannot be separated because both have a close relationship as an ecosystem. The purpose of this study was to determine: 1) the level of social and ecological resilience; 2) Scenarios on ecological and social factors for the sustainability of protected forests. The research method uses survey methods and data analysis uses qualitative-verification analysis based on the results of the calculation of the resilience index and the phase of the socio-ecological system. The results showed that the level of social and economic resilience was partially or simultaneously at the level of resilience with their respective indexes: social: 0.6944); ecology: 0.8148 and socio-ecology 0.7460. The exploitation phase (growth) leads to the conservation phase. The results of the scene show that both of them are at a high level of resilience with a resilience index of 0.8889 (high resilience) and a reorganization phase. If this phase can be maintained with various management interventions according to its function, it will minimize the level of disturbance to the Mount Sirimau Protection Forest Group.